Faculty computer-mediated communication apprehension during shift to emergency remote teaching: implications for teacher-student interactions and faculty organizational outcomes - Farris, Kristen LeBlanc; Dye, Luke A.; Houser, Marian L.; Timmerman, C. Erik (Frontiers in Communication, 2024)
Guided by the model of faculty readiness for online teaching (FROT; Martin et al., 2019), the goal of the current study was to investigate the influence of instructors’ knowledge (e.g., online teaching preparation), confidence (e.g., computer-mediated communication apprehension; CMCA), and attitudes about online teaching (e.g., perceived usefulness) on their communicative and organizational outcomes (e.g., communication frequency and satisfaction, job satisfaction, motivation). We recruited 206 college instructors from a variety of institutions to report on their experiences during the transition to emergency remote teaching in the spring 2020 academic semester. Results from the study suggest that instructors’ CMCA was a significant and negative predictor of instructors’ communication satisfaction with online student interactions, job satisfaction, and motivation to teach after controlling for the other predictors in the model. Taken together, the findings suggest that CMCA may serve as a barrier to instructor communication competence in online teaching and may have deleterious impacts on instructor affect toward their positions. Ultimately, we recommend that faculty workshops aimed at developing online teaching competence should specifically address instructor dispositional and affective characteristics such as CMCA to prevent faculty vulnerability.